THE IMPACT OF WORK ENVIRONMENT, COMMUNICATION AND LEADERSHIP ON PERFORMANCE OF EMPLOYEES IN TARAKAN CITY EDUCATION OFFICE - Pendi Tandi Bua; Theodorus Kristianto; Achmad Daengs GS (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2020)
This study  aims to  examine and analyze the influence  of the working environment of communication  and  leadership to wards the  performance of employees in the education department  of Tarakan  city. Data  collection  was done by distributing questionnaires and  carried out  on 48 people who were samples in this  research. The sample  technique  used is random  and data testing  techniques  used in this research include validity test with factor analysis, reliability test with Alpha Cronbach. Multiple linear regression analysis. The results of the t test showed that the partial variable of the working environment has positive and significant effect on the performance  of employees in the education departmet of tarakan city, so the hypothesis in the proposed proved true (T-test = 2,731 > T-table  2.012) .T test results showed that the communication variables have a positive and significant impac on the performance of employees in the education  departmet  of tarakan  city, so the hypothesis  in the proposed proved true (T-test  = 3,339 > T-table   2.012). T test results  showed that  the Leadership to word variables have a positive and significant impac on the performance of employees  in the education  departmet  of tarakan  city, so the hypothesis in the proposed proved  true  (T-test  = 2,846  > T-table   2.012)  The results of f test showed that the working enviroment  of comunication  and leadership  positiv  effect  and  significant  to the  performance of employees in the education departmet  of tarakan  city , so the hypothesis  in the proposed proved true  (F-test = 81,195 > F-tabel 2,82).